5G AND BEYOND WIRELESS COMMUNICATIONS fundamentals, applications, and challenges - Bhowmick, Abhijit; Choukiker, Yogesh Kumar; Singh, Indrasen; Nallanathan, Arumugam (CRC PRESS, 2024)
This book provides a thorough introduction of 5G and B5G wireless networks, as well as cutting-edge technologies that aid in network design and development. This book also covers machine learning techniques for advanced communications. 5G and Beyond Wireless Communications: Fundamentals, Applications, and Challenges discusses the newest technologies for 5G and future networks, including CR networks, D2D networks, UAV-assisted communications, RIS-assisted communications, and ML for communication networks. Additionally, it discusses using antenna systems for advanced communications networks. It also explores various security issues and their solutions, as well a power and interference management and machine learning for optimization of network parameters. The book also examines the design of 5G antennas from a materials perspective, and a thorough analysis of the materials utilized to create innovative antennas for advanced communication network is discussed. The book concludes by discussing the advancement of ML-based communication networks and their future opportunities and challenges. This book will be helpful for researchers and master students who want to focus their research work in the area of next-generation advanced wireless communications.
Keywords: Wireless communication systems; Transmission sans fil; TECHNOLOGY / Telecommunications